Households’ perception and willingness to pay for bread with cassava flour inclusion in Oshogbo Metropolis, Osun state, Nigeria (2014)
The rising cost of wheat importation for the production of bread, a well-established and accepted food product relished by the general public, has been a matter of great concern to the Nigerian Government in recent times. This has led to the increased interest in cassava flour which has been identified as a close, cost-effective substitute to wheat flour in bread production. Motivated by the far-reaching benefits of the new cassava policy on the substitution of wheat flour with cassava flour in bread production to the economy, a logistic regression model was employed to examine households’ perception and willingness to pay for bread with cassava flour inclusion in Osogbo Metropolis, Osun State, Nigeria. Findings suggest that bakery owners adopting the use of cassava flour in bread production pay careful attention to the taste, packaging, size, colour and price of the bread since these variables affect the buying decisions of the consumers. While consumers’ willingness to pay a premium varied with degrees of cassava flour inclusion, households’ willingness to pay showed a negative relationship with the premium price and a positive significant relationship with household income and share of bread in total household food expenditure. Thus, proper attention should be given to the variables affecting the buying decisions of consumers, price stabilization of bread with cassava flour inclusion as well as the design of empowerment programmes targeted at increasing household income.